A historical perspective of entrepreneurship in Angola - Pereira, R. (JANUS.NET, e-journal of International Relations, 2020)
This article makes a historical analysis of entrepreneurship in Angola, starting from the historical evolution of the entrepreneurship concept to focus on the evolution of this phenomenon in Angola, over four different historical periods. Resorting to bibliographic sources of reference authors and their extensive analysis, it was possible to obtain a historical perspective of entrepreneurship in Angola. The paper critically examines its evolution in the country and provides a reflection on possible future development scenarios.